THE EFFECT OF PERCEIVED CONVENIENCE, SATISFACTION, AND TAX UNDERSTANDING ON INTEREST IN USING E-FILING AT WPOP WITH THE BENEFITS OF INFORMATION TECHNOLOGY AS A MODERATING VARIABLE - Cindy Della Ardana; Yunita Fitria (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2025)
This study aims to analyze and prove the effect of perceived convenience, satisfaction, and tax understanding on interest in using e-Filing for individual taxpayers (WPOP) registered at KPP Pratama Tenggarong. This study uses primary data collected through questionnaires that have been conducted by researchers directly or offline and questionnaires sent online using google forms. The number of samples used in this study were 100 respondents selected through purposive sampling technique of individual taxpayers registered at KPP Pratama Tenggarong and who reported their annual tax return using e-Filing. This study uses SmartPLS version 4.1 for data analysis and is measured using a Likert scale. The results of this study indicate that perceived convenience, perceived satisfaction, and understanding of taxes have a significant positive effect on interest in using e-Filing on individual taxpayers, the benefits of information technology do not play a role in moderating the effect of perceived convenience, perceived satisfaction, and understanding of taxes on interest in using e-Filing on individual taxpayers.